Complete proximal hamstring avulsions: is there a role for conservative management? A systematic review of acute repairs and non-operative management. Issue 1 (5th January 2017) - Buckwalter, Joseph; Westermann, Robert; Amendola, Annunziato
Abstract : Importance: Presently, acute surgical repair (within 4–6 weeks) of complete, proximal hamstring avulsion is the recommended treatment. No systematic review to date has evaluated patient satisfaction and return to sport after acute repair of complete, proximal hamstring avulsion injury. Objective: To systematically review the current evidence regarding management of complete, proximal hamstring avulsion injuries in relation to patient satisfaction and return to sport. Evidence review: PubMed, CINAHL, SPORTDiscus, EMBASE and Cochrane library were searched systematically for relevant studies through October 2015. Two authors independently screened the results and identified studies meeting inclusion criteria. Included studies were reviewed for patient satisfaction and return to sport outcomes, and their results are reported. Findings: A total of 22 studies (262 participants) were identified in this review. Only 4 studies, totalling 24 patients, reported on non-operative management, while 18 studies, totalling 238 patients, reported on operative management of complete, proximal hamstring avulsions. No identified study specifically measured patient satisfaction and return to sport in a prospective or case–controlled manner. Most studies were case reports with low level of evidence. Patient satisfaction after acute repair of complete, proximal hamstring avulsion ranged from 80% to 93% and return to sport was 94.5%. Non-operative management resulted in lower patient satisfaction (16.7%) and return to sport (54.2%). Conclusions and relevance: Acute surgical repair (within 4–6 weeks) of complete, proximal hamstring avulsion injuries results in high patient satisfaction and high level of return to preinjury sporting level, when compared to non-operative treatment. No conclusions regarding surgical repair of incomplete hamstring avulsion injuries or type of repair could be drawn from this review. More prospective data would be of value, as acute repair of complete, proximal hamstring avulsions appears to result in better outcomes than non-operative management, but any conclusion regarding comparison is limited due to the dearth of non-operative management studies and the high risk of bias. Level of evidence: Level IV.